MALATHİON'UN PULLU SAZAN (CYPRİNUS CARPİO LİNNAEUS, 1758)'DA PARAOKSONAZ VE ARİLESTERAZ ENZİM AKTİVİTELERİNE ETKİSİNİN ARAŞTIRILMASI - DERİCİ, TUĞÇE (Fırat Üniveristesi, 2016)
Bu çalışmada, pullu sazan (Cyprinus carpio)'a farklı konsantrasyonlarda uygulanan malathionun paraoksonaz (PON) ve arilesteraz (ARE) enzim aktivitelerine etkisinin ortaya çıkarılması amaçlandı. Bunun için malathionun letal konsantrasyon (LC50) değerinin 1/2'si 1/4'ü ve 1/8'i üç deneme grubuna 21 gün süreyle uygulandı. Malathion uygulanan ve kontrol grubundaki balıklardan 7., 14., ve 21. günlerde serum ve karaciğer örnekleri alındı. Alınan örneklerde PON ve ARE enzim aktivitelerindeki değişimler belirlendi. Malathion uygulanan grupların serum ve karaciğerindeki PON ve ARE enzim aktiviteleri kontrol grubuna kıyasla azaldı (p < 0.05). Bu azalma 7. ve 14. günlerde kontrol grubundan istatistiksel olarak farklı bulundu (p < 0.05). 21. günde ise bu aktivitelerde herhangi bir fark bulunmadı (p > 0.05). Anahtar Kelimeler: Arilesteraz, Cyprinus carpio, Enzim

In this study, it was aimed to reveal the effects on paraoxonase (PON) and arylesterase (ARE) enzyme activities of malathion applied in different concentrations in scaly carp (Cyprinus carpio). For this purpose, 1/2, 1/4 and 1/8 of LC50 concentration value of malathion were exposed to three experimental groups for 21 days. Serum and liver samples on 7, 14 and 21 days collected from fish in the control group and experimental groups which exposed to malathion. Changes in the PON and ARE enzyme activities were determined in the serum and liver samples which collected from fish. The PON and ARE activities in the serum and liver decreased in the groups exposed to malathion compared to that of the control group (p < 0.05). This reduction was statistically different from the control group on 7 and 14 days (p < 0.05). There was no difference in these activities on 21 day (p > 0.05). Key words: Arylesterase, Carp, Cyprinus carpio, Enzyme, Malathion, Pesticide, Paraoxonase.
Investigation of effect of Malathion on paraoxonase and arylesterase enzyme activities in scaly carp (Cyprinus carpio Linnaeus, 1758)
Keywords: Su Ürünleri